2007
DOI: 10.46867/ijcp.2007.20.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Do Dolphins Eavesdrop on the Echolocation Signals of Conspecifics?

Abstract: We are grateful to Christer Blomqvist for his helpful comments on earlier versions of this manuscript. Thanks also to several anonymous reviewers for helpful comments and suggestions. This paper represents contribution #101 of the Dolphin Communication Project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Comparative studies of the behavior and communication of captive and wild dolphins can be complimentary and provide a more complete and comprehensive understanding of both individual and group behavior. More than 20 years of observations on dolphins in both settings have informed the author's view with respect to conducting research on animals in both venues (Beard, 2007;Beard et al, in review;Dudzinski, 1996Dudzinski, , 1998Dudzinski et al, 2003Dudzinski et al, , 2009Gregg et al, 2007Gregg et al, , 2008Kogi et al, 2004;Melillo et al, 2009;Paulos et al, 2008). Additionally, a survey of marine animal trainers confirmed that both researchers and animal care professionals can use information and results from wild animals to inform enrichment and assessment of animal behavior for individuals in the captive arena: categorization and qualification of behaviors was essentially the same for researchers observing wild dolphin behavior from under water as for trainers who work with dolphins every day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative studies of the behavior and communication of captive and wild dolphins can be complimentary and provide a more complete and comprehensive understanding of both individual and group behavior. More than 20 years of observations on dolphins in both settings have informed the author's view with respect to conducting research on animals in both venues (Beard, 2007;Beard et al, in review;Dudzinski, 1996Dudzinski, , 1998Dudzinski et al, 2003Dudzinski et al, , 2009Gregg et al, 2007Gregg et al, , 2008Kogi et al, 2004;Melillo et al, 2009;Paulos et al, 2008). Additionally, a survey of marine animal trainers confirmed that both researchers and animal care professionals can use information and results from wild animals to inform enrichment and assessment of animal behavior for individuals in the captive arena: categorization and qualification of behaviors was essentially the same for researchers observing wild dolphin behavior from under water as for trainers who work with dolphins every day.…”
Section: Discussionmentioning
confidence: 99%
“…The summary video was 25-minutes representing the behavior of three dolphin species recorded underwater in three geographic locations: Atlantic spotted dolphins (Stenella frontalis) -Bahamas, Indo-Pacific bottlenose dolphins (Tursiops aduncus) -Mikura Island, Japan, and dusky dolphins (Lagenorhynchus obscurus) -Patagonia, Argentina. All video records were gathered during studies of dolphin behavior and communication inclusive from 1992 to 2001 (Dudzinski, unpublished video data; see also Dudzinski, 1998;Gregg, Dudzinski, & Smith, 2007;Paulos, Dudzinski, & Kuczaj, 2008;Dudzinski et al, 2009Dudzinski et al, , 2010. With graduate students in the Psychology Department of the University of Southern Mississippi, two surveys were developed, one brief and one detailed.…”
Section: Trainer Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in recent years has resulted in significant increases in the understanding of the acoustic characteristics of both echolocation clicks and the subsequent returning echoes (Au, 1993;Au & Hastings, 2008;Au et al, 2008;Houser, Helweg & Moore, 1999;Houser et al, 2005;Moore, 1997;Moore, Dankiewicz, & Houser, 2008), as well as an appreciation of the dolphin ability to eavesdrop on the echoes that result from the clicks produced by another dolphin (Götz, Verfaß, & Schnitzler 2005;Gregg, Dudzinski, & Smith, 2007;Xitco & Roitblat, 1996). However, at the present time we know little about the manner in which information is represented and used by dolphins (Harley, Xitco, & Roitblat, 1995;Popper, Hawkins, & Gisiner, 1997;Roitblat, Helweg, & Harley, 1995;Roitblat, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…That the listener was able to get enough information to identify an object is somewhat remarkable given the directionality of the dolphin echolocation system; echoes received 10° off-axis can have a much lower intensity (-10 dB) with substantially lower frequencies (-114 kHz peak frequency) (Au, 1993) than on-axis echoes. Determining that dolphins can eavesdrop on the echoes of neighbors required -336 -careful experimental work with captive dolphins that allowed later related work to occur through observational studies of wild dolphins (Gotz, Verfuss, & Schnitzler, 2005) as well as inspiring more theoretical work on the topic (Gregg, Dudzinski, & Smith, 2007).…”
Section: Echolocationmentioning
confidence: 99%